Influence of deprivation and rurality on patient-reported outcomes of men living with and beyond prostate cancer diagnosis in the UK: A population-based study. (December 2020) - Smith, Lesley; Downing, Amy; Norman, Paul; Wright, Penny; Hounsome, Luke; Watson, Eila; Wagland, Richard; Selby, Peter; Kind, Paul; Donnelly, David W.; Butcher, Hugh; Huws, Dyfed; et al.
Highlights: National study exploring the impact of deprivation and rurality on health-related quality of life following prostate cancer. The impact of deprivation and rurality on HRQL was not greater than would be expected in the general population. Some functional prostate specific outcomes were affected by deprivation. No clinically meaningful differences in HRQL were identified by rurality of residence. Abstract: Background: In the UK, inequalities exist in prostate cancer incidence, survival and treatment by area deprivation and rurality. This work aimed to identify variation in patient-reported outcomes of men with prostate cancer by area type. Methods: A population-based survey of men 18–42 months after prostate cancer diagnosis (N = 35608) measured self-assessed health (SAH) using the EQ-5D and five functional domains using the Expanded Prostate Cancer Index Composite (EPIC-26). Results: Mean SAH was higher for men in least deprived areas compared to most deprived (difference 6.3 (95 %CI 5.6–7.2)). SAH scores were lower for men in most urban areas compared to most rural (difference 2.4 (95 %CI 1.8–3.0)). Equivalent estimates in the general population reported a 13 point difference by deprivation and a 4 point difference by rurality. For each EPIC-26 domain, functional outcomes were better for men in the least deprived areas, with clinically meaningful differences observed for urinary incontinence and hormonal function. There were no clinically meaningful differences in EPIC-26 outcomes by rurality with less than a three point difference in scores for each domain between urban and rural areas. Conclusion: In men 18–42 months post diagnosis of prostate cancer in the UK, impacts of area deprivation and rurality on self-assessed health related quality of life were not greater than would be expected in the general population. However, clinically meaningful differences were identified for some prostate functional outcomes (urinary and hormonal function) by deprivation. No impact by rurality of residence was identified.